Efficiency of Watering on Cacao Seedling Inoculated with Mycorrhiza - Yeni Lucia; Sudirman Yahya; M. Yahya Fakuara (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1998)
The use of mycorrhiza-plantation crop association has not been widely applied, due to lack of information on the positive effect of the association on the tree crops. The plastic house study was established to evaluate the effect of inoculation of mycorrhiza fungi on the watering efficiency of cacao seeding. Four inoculation treatment of mycorrhiza fungi: without inoculant (control), endomycorrhiza (Gigaspora margarita), ectomycorrhiza (Scleroderma columnare) and double inoculant of both species, were combined on factorial arrangement with four rates of watering interval: once of every 1, 3, 5, and 7 days. Inoculation significantly improved seedling growth as shown by plant height, leaf area and dry shoot weight compared to control treatment. Double inoculation had the best result, followed by endomycorrhiza and ectomycorrhiza, consequtively. Inoculation also significantly increased watering efficiency on cacao nursery as many as 2 to 4 times compared to control and shortened the time of nursery period as long as one month.